Pengaruh Persepsi Kemudahan Penggunaan, Persepsi Efektivitas Dan Persepsi Manfaat Terhadap Minat Penggunaan QRIS Sebagai Alat Transaksi Pembayaran Pada Mahasiswa Universitas Buana Perjuangan Karawang - Siti Amamilah; Dedi Mulyadi; Santi Pertiwi Hari Sandi (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to determine the effect and analyze the variables of perceived ease of use, perceived effectiveness and perceived benefits on interest in using the Quick Response Code Indonesian Standard (QRIS) as a payment transactions tool for 2019-2020 class students at Buana Perjuangan University, Karawang. In addition, this study also aims to determine the factors that most influence the intention to use QRIS. This study uses a descriptive verification method with a quantitative approach, with a sampling technique that is purposive sampling and uses the slovin formula. This research was conducted using a likert scale questionnaire which was distributed via google form to 100 respondents to management student from the 2019-2020 class of Buana Perjuangan University, Karawang. The data analysis technique uses path analysis with partial and simultaneous hypothesis testing. The results showed that there was a positive relationship between variables X1 and X2, X1 and X3, and X2 and X3. Partially, perceived ease of use has no effect and is not significant on interest in using QRIS. Then the perception of effectiveness partially has no effect and is not significant on the intention to use QRIS and the perceived benefits partially have a positive and significant effect on the intention to use QRIS. Then simultaneously the variables perceived ease of use, perceived effectiveness, and perceived benefits have a significant influence on interest in using QRIS. Keywords: perceived ease of use, perceived effectiveness, perceived benefits and interest in using the QRIS